2021
DOI: 10.1007/s11356-021-16960-2
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting carbon emissions due to electricity power generation in Bahrain

Abstract: Global warming and climate change have become one of the most embarrassing and explosive problems/challenges all over the world, especially in third-world countries. It is due to a rapid increase in industrialization and urbanization process that has given the boost to the volume of greenhouse gases (GHGs) emissions. In this regard, carbon dioxide (CO 2 ) is considered a significant driver of GHGs and is the major contributing factor for global warming. Considering the goal of mitigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Previous studies identified that urbanization (Balsalobre-Lorente et al, 2021;Qader et al, 2021), institutional quality (Usman and Jahanger, 2021), renewable/nonrenewable/total energy consumption (Usman et al, 2020;Hussain and Rehman, 2021;Regmi and Rehman, 2021;Rehman et al, 2021a;Rehman et al, 2021b), and trade (Rehman et al, 2021c;Rehman et al, 2021d; are more influencing factors that affect CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Previous studies identified that urbanization (Balsalobre-Lorente et al, 2021;Qader et al, 2021), institutional quality (Usman and Jahanger, 2021), renewable/nonrenewable/total energy consumption (Usman et al, 2020;Hussain and Rehman, 2021;Regmi and Rehman, 2021;Rehman et al, 2021a;Rehman et al, 2021b), and trade (Rehman et al, 2021c;Rehman et al, 2021d; are more influencing factors that affect CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, the usage of CO 2 emissions as a proxy to capture the environmental damage caused by economic growth received massive criticism and represented a vast debatable topic. Many researchers argued that CO 2 only captures a part of the considerable damage caused by the economic growth that is, ruining the planet (Kamal et al, 2021;Khalid et al, 2021;Qader et al, 2021;. Furthermore, from a sustainability point of view, CO 2 is not a suitable measure of remnants induced by economic progress.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of countries have incorporated environmental factors into an important part of trade regulation (Baghdadi et al 2013;Usman et al 2021a). In 2019, the concentration of carbon dioxide in the global atmosphere reached the highest level in 3 million years, and air pollution poses a great threat to human health and even life (Qader et al 2021;Usman et al 2021b;Jahanger et al 2021aJahanger et al , 2021bYang et al 2021aYang et al , 2021b. As the world's largest exporter and the world's largest carbon emitter, the Chinese government has set higher requirements for energy conservation, emission reductions, and environmental regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating ecological regulation into the analysis framework of export trade can better change the mode of economic development and thus alleviate the contradiction between economic development and ecological environment (Usman et al 2020a). At present, although the effect of environmental regulation has been improved, the overall effect is not satisfactory (Kamal et al 2021;Zhao et al, 2021;Yang et al, 2020;Jahanger 2021aJahanger , 2021bQader et al 2021). So, in the field of export, is environmental regulation helpful to China's export of goods and improve the export competitiveness of enterprises?…”
Section: Introductionmentioning
confidence: 99%